An implied reader’s reading? – A reception-oriented analysis of New Zealand identities (KULT_online, 2010)
Christina Stachurski is an award-winning playwright and theatre director teaching modern drama and creative writing at Canterbury University. Reading Pakeha? is based on her doctoral thesis and is her first book-length foray into the field of fictional analysis. By combining Iser’s theory of implied readership with an author- and reception-centred approach, Stachurski studies the role of fictional representations in the shaping of New Zealand identities over various decades. More precisely, she tries to deduce through (con)textual analysis general reader responses to three canonical New Zealand novels published between 1939 and 1990. Stachurski successively analyses these works of fiction by comparing them with each other and with other New Zealand novels (and feature films) of the period as well as the settler/societal contexts of Australia and Canada. In so doing, she identifies the wide range of readerships these novels cater to while tracing changes to the understanding of the term ‘Pakeha’ over time.